A novel formation pathway of Nε-(carboxyethyl)lysine from lactic acid during high temperature exposure in wheat sourdough bread and chemical model. (15th September 2022) - Zhang, Zhongfei; Cheng, Weiwei; Wang, Xiaowen; Wang, Mingfu; Chen, Feng; Cheng, Ka-Wing
Graphical abstract: Highlights: Lactic acid contributes to the carbon skeleton of CEL in sourdough bread. Lactic acid preferentially promotes CEL formation in sourdough bread. Lactic acid-mediated CEL formation with lysine could be independent of GO and MGO. Abstract: N ε -(carboxymethyl)lysine (CML) and N ε -(carboxyethyl)lysine (CEL) have been the most extensively studied advanced glycation end-products (AGEs) in foods. Their formation mechanism, especially the latter, has not been clearly delineated in fermented food. In this work, the relative contents of CEL and CML were evaluated in a sourdough-bread and a silica solid chemical model. Lactic acid (LA) content in the sourdough increased with fermentation time that was accompanied by an increase in CEL, but not CML content in the bread. The role of LA as a precursor for CEL was supported by a positive significant correlation between LA and CEL contents, and further analysis using isotope-labeled LA (LA- 13 C3 ) revealed that the three carbon atoms of LA were incorporated into CEL. These findings for the first time indicate LA may function as a precursor to promote CEL formation in sourdough bread that merits further investigation.